Estimating malaria parasite density among pregnant women at central Sudan using actual and assumed white blood cell count - Haggaz, AbdElrahium D (BioMed Central, 2014)
BACKGROUND: Microscopic examination using Giemsa-stained thick blood films remains the reference standard for detection of malaria parasites and it is the only method that is widely and practically available for quantifying malaria parasite density. There are few published data (there was no study during pregnancy) investigating the parasite density (ratio of counted parasites within a given number of microscopic fields against counted white blood cells (WBCs) using actual number of WBCs. METHODS: Parasitaemia was estimated using assumed WBCs (8,000), which was compared to parasitaemia calculated based on each woman’s WBCs in 98 pregnant women with uncomplicated Plasmodium falciparum malaria at Medani Maternity Hospital, Central Sudan. RESULTS: The geometric mean (SD) of the parasite count was 12,014.6 (9,766.5) and 7,870.8 (19,168.8) ring trophozoites /μl, P <0.001 using the actual and assumed (8,000) WBC count, respectively. The median (range) of the ratio between the two parasitaemias (using assumed/actual WBCs) was 1.5 (0.6-5), i e, parasitaemia calculated assuming WBCs equal to median (range) 1.5 (0.6-5) times higher than parasitaemia calculated using actual WBCs. There were 52 out of 98 patients (53%) with ratio between 0.5 and 1.5. For 21 patients (21%) this ratio was higher than 2, and for five patients (5%) it was higher than 3. CONCLUSION: The estimated parasite density using actual WBC counts was significantly lower than the parasite density estimated using assumed WBC counts. Therefore, it is recommended to use the patient`s actual WBC count in the estimation of the parasite density.